2016
DOI: 10.1016/j.jtho.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Advanced Non–Small Cell Lung Cancer: Are Research Biopsies a Barrier to Participation in Clinical Trials?

Abstract: A growing number of NSCLC trials are requiring tumor tissue for treatment eligibility, which appears to be a significant barrier to trial enrollment. Potential solutions include use of available diagnostic samples (e.g., cytology samples), development of peripheral blood assays for molecular markers, faster central laboratory testing turnaround time, and more resources for rapid biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 17 publications
0
45
0
2
Order By: Relevance
“…The limitations of tumor biopsies have recently been supported by a study that demonstrated up to 30% of patients at a community-based academic center did not undergo guidelinerecommended molecular testing, despite an institutional reflex testing policy for tissue [66]. In addition, repeat tissue acquisition poses barriers to clinical trial enrollment, as demonstrated by a recent study retrospectively evaluating patient enrollment to 55 clinical trials at a single Canadian institution in which fewer patients received study treatment in trials mandating tissue specimens compared with trials that did not (55% vs. 83%; p , .001) [67]. Plasma cfDNA platforms offer promise in overcoming these challenges by rapidly genotyping treatment-naïve and -refractory patients and might eventually obviate the need for the repeat biopsies mandated by many clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of tumor biopsies have recently been supported by a study that demonstrated up to 30% of patients at a community-based academic center did not undergo guidelinerecommended molecular testing, despite an institutional reflex testing policy for tissue [66]. In addition, repeat tissue acquisition poses barriers to clinical trial enrollment, as demonstrated by a recent study retrospectively evaluating patient enrollment to 55 clinical trials at a single Canadian institution in which fewer patients received study treatment in trials mandating tissue specimens compared with trials that did not (55% vs. 83%; p , .001) [67]. Plasma cfDNA platforms offer promise in overcoming these challenges by rapidly genotyping treatment-naïve and -refractory patients and might eventually obviate the need for the repeat biopsies mandated by many clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Then, only the cases relating to subjects with locally advanced or metastasized diagnosis [15] eligible for the first line of treatment [3] were considered. It is estimated that 85% of these patients are eligible for the tissue biopsy [2], while the remaining 15% potentially to the liquid biopsy only. Among the patients who perform the tissue biopsy, the outcome may not be determinable in 30% of cases [16].…”
Section: Populationmentioning
confidence: 99%
“…Actually, the number of clinical trials they have been able to facilitate so far is rather low compared to the investment [32]. Working on complex platforms, which are centred on the biology of the disease is challenging, as the current regulatory field in Europe is not ready to optimally accommodate them [33,34]. Europe should give consideration to developing solutions to efficiently sort patients and screen and provide access to European biology-based clinical trials which would be plugged into such coordinating infrastructure [35].…”
Section: A Proposal For Building a Large-scale Interconnected Platformentioning
confidence: 99%